PROFITABILITAS DAN EFISIENSI USAHATANI BAWANG MERAH - Imron Rosyadi; Daryono Soebagyo; - Suyatmin (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2015)
The purpose of this research is to determine and analyze the profitability and performance of onionfarming marketing margins; analyze and know the parts of prices received by farmers (farmer'sshare) and analyze the efficiency of onion farming in the district of Brebes. Samples taken in thisstudy is 30 onion farmers in the district of Brebes, who settled in six (6) Village, each village wastaken 5 farmers as the research sample. These results indicate that the location of onion farmingresearch does not provide benefits Significant (unprofitable) to the household economy of farmers.The high selling prices at the retail level and supermarkets do not have a significant impact on thelevel of profits of farming in the study area. Farming is done by farmers in the study area isinefficient. Onion marketing chain in the study area is relatively long, which consists of 4 lines ofmarketing: (i) farmers, traders, retailers in Brebes, end consumers in Brebes; (ii) farmers,wholesalers, traders in the central market Kramat Jati, market retailers outside of Jakarta, thefinal consumer in and outside Jakarta; (iii) farmers, traders in the central market Kramat Jati,market retailers outside of Jakarta, the final consumer in and outside Jakarta; and (iv) farmers,wholesalers, traders between islands outside Java vendors, and end users outside Java.Keywords: farming onion, profitability, efficient, output-input